Pure Duplication of the Distal Long Arm of Chromosome 15 with Ebstein Anomaly and Clavicular Anomaly - O'Connor, Rachel; Al-Murrani, Amel; Aftimos, Salim; Asquith, Philip; Mazzaschi, Roberto; Eyrolle-Guignot, Dominique; George, Alice M.; Love, Donald R. (Case Reports in Genetics, 2011)
This report is of a patient with pure trisomy of 15q24-qter who presents with the rare Ebstein anomaly and a previously unreported skeletal anomaly. Chromosome microarray analysis allowed high-resolution identification of the extent of the trisomy and provided a means of achieving higher-resolution breakpoint data. The phenotypic expression of unbalanced chromosomal regions is a complex phenomenon, and fine mapping of the involved region, as described here, is only a first step on the path to its full understanding. Overexpression of the LINGO-1 and CSPG4 genes has been implicated in developmental delay seen in other patients with trisomy of 15q24-qter, but our patient is currently too young to ascertain developmental progress. The genetic underpinning of Ebstein anomaly and the skeletal anomaly reported here is unclear based on our high-resolution dosage mapping.